Deleuze: A Critical Reader - Patton, Paul (Oxford Blackwell, 1996)
Paul Patton brings together an outstanding collection of appraisals by French- and English-speaking scholars of Gilles Deleuze (1925-1995), one of the most important post-war French philosophers. A number of these pieces address Deleuze's original interpretations of key figures in the history of philosophy, including Spinoza, Kant, Hegel and Bergson. Others discuss his work on mathematics, and the relevance of his conceptual creativity for art criticism, feminist, literary, and cultural studies. Several of the contributions here have not been previously published.
Keywords: Deleuze, Gilles -- 1925-1995; 20th Century (1901-2000); Philosophy